Evaluation of quality of life in psychiatric veterans of Isfehan - Kh. Ahmadi; v. Nejati (Afarand Scholarly Publishing Institute, 2010)
Background and Purpose: Evaluation of quality of life of psychiatric veterans can use as guidance for programming of their health. The purpose of current study is evaluation of quality of life in psychiatric veterans of Isfehan. Method: In this cross sectional study we evaluate 345 psychiatric veterans of Isfehan in 2008 that were participated in veteran's health monitoring project. We complete SF36 questionnaire in their home with face to face interview. Results: Findings show that in dimensions of quality of life only physical activity is proper and other dimensions is very low. Age, marriage and occupation was related to quality of life. Discussion: Aging and early retirement of psychiatric veterans are common treat for their quality of life. Seriously intervention should be designed for promotion of quality of life in psychiatric veterans